The knowledge of entry mode decision for small and medium enterprises - Feng-Jyh Lin; Ching Wei Ho (Journal of Innovation & Knowledge (JIK), 2019)
A suitable organizational structure is necessary for companies to effectively manage foreign activities. Firms can choose from among several modes of foreign market entry, including exporting, contractual agreements, joint venturing, acquiring an existing company, and establishing a wholly owned greenfield investment from scratch. However, the majority of literature on foreign market entry mode choices has focused on large multinational enterprises. Small and medium enterprises (SMEs) with limited financial and personnel resources are likely to base their foreign market entry mode choice on the resources available. Building on a literature review, this study analyzes the determinants of SMEs' foreign market entry mode. The findings suggest that innovation, product characteristics, advertising intensity, export intensity, and industry have positive effects on the high-level resource commitment choice in foreign markets.
Keywords: F23; M16; 650; Small and medium enterprises; Foreign market entry mode; Internalization